A Further Fragment of the Abridged Version of Cassiodorus's Commentary on the Psalms. (6th December 2020) - Imhoff, Helen
ABSTRACT: Hessisches Staatsarchiv Marburg Hr 2, 19 is a recently described fragment of the abridged version of Cassiodorus's Expositio psalmorum, as found in Durham, Cathedral Library, MS. B II. 30. In the past, it has been debated whether the abridged commentary ever existed in more than one copy, the focus being on the relationship between the fragment Landesbibliothek Düsseldorf K16:Z03/01 and Durham MS. B II. 30. This note argues that Hr 2, 19 provides evidence that at least three or perhaps four copies existed. An appendix provides a transcription, images of the fragment, commentary on variants, and corrections made in Hr 2, 19 and the Durham manuscript.